THE EFFECT OF WORKING CAPITAL TO TOTAL ASSET (WCTA) AND NET PROFIT MARGIN (NPM) ON THE RETURN STOCK OF PT ANEKA TAMBANG, TBK - Fahira, Nur Ihsan; Hendra, Endang (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Investment is the placement of a number of funds or other resources carried out in the present to get future profits. Investors who invest in companies must know the factors that can cause profits or losses when investing. One of the factors that investors can consider to carry out investments is understanding financial statement information to determine the effectiveness of the company in generating the value of Working Capital to Total Assets (WCTA) or the company’s ability to use the company’s current assets, knowing the Net Profit Margin (NPM) to assess the company’s ability to generate profits,Â as well as knowing the level of profit on the capital invested in the investment or Stock Return. The results indicated that partial Working Capital to Total Assets (WCTA) had no significant effect on Stock Return with a coefficient of determination of 8.2%. Partially, Net Profit Margin had no significant effect on Stock Return with a coefficient of determination of 12.5%. Thus simultaneously, Working Capital to Total Assets (WCTA) and Net Profit Margin had no significant effect on Stock Return with a coefficient of determination of 25.3%. Keywords: Working Capital to Total Asset (WCTA), Net Profit Margin (NPM), Stock Rteurn